REGULASI DAN PERLINDUNGAN HUKUM DALAM TRANSAKSI DIGITAL PAYMENT DI OTORITAS JASA KEUANGAN DAN BANK INDONESIA CABANG KEDIRI - Musonnif, Ahmad; Aibak, Kutbuddin (Ahkam: Jurnal Hukum Islam, 2019)
Lately, we’ve heard a lot about the so-called "micin generation". A generation where everything is judged and based on technology. Some say that the current generation is a generation with their heads down, where bowing is not interpreted as manners or shame, but looking at the mobile phone screen endlessly. This turns out to be not just a mere nickname but indeed this is a real picture of the development of technology today. Technology dominates almost everything, even from some unexpected angles. This problem is the reason why it is very necessary to study the implementation of regulations and legal protection of digital payment transactions carried out in the community. Most people are very unfamiliar with economic issues and digital payment issues. It is necessary to give a clear understanding of digital payment because people often access everything using the internet without ever knowing the impact they will receive in the future.